The Demineralization Optimization for Chitosan Synthesis from Crab Shell Waste (Portunus pelagicus) - Intan Permata Sari; Esti Mulatsari; Esti Mumpuni; Agus Purwanggana (LPPM Universitas Abdurrab, 2024)
Chitosan, gelatin, albumin, and sodium alginate are examples of natural polymers that are often utilized as a basis material for polymeric nanoparticles. The deacetylation of chitin molecules produces the formation of chitosan. Chitin, protein, CaCO3, MgCO3, and astaxanthin pigment are all found in crab shells. Crab shell is an undervalued potential waste. Despite the fact that copious crab shell waste can be used to produce raw materials and industrial products. According to the findings of Mohadi et al (2014), chitosan was extracted with a yield of 70.71% and a deacetylation degree of 76.6%. Previous research on optimizing chitosan synthesis has involved changing the base reagent at the deacetylation stage. The results showed that a 50% concentration of KOH reagent produced the best chitosan properties. Another study on the synthesis of chitosan from crab shells got a yield of 70.4%, and the following analysis showed that this high yield is due to the amount of calcium. Therefore, demineralization in the synthesis of chitosan from crab shells must be optimized. The calcium content was measured after optimization with various solvent concentration variations. The best demineralization optimization results use 3 M hydrochloric acid with a decrease in calcium content of 97.75%.